Tinjauan Hukum Ekonomi Syariah Terhadap Mekanisme Penjualan Karya atau Kreasi Digital Berbasis NFT (Non Fungible Token) Pada Platform Opensea - Hartinah Aprilia; Muhammad Zaki; Liky Faizal (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to determine the selling mechanism and to understand the reflection of sharia economic law on the mechanism for selling Non-Fungible Token (NFT)-based digital works/creations on the Opensea Platform. This research includes library research (library research) which uses secondary data consisting of three legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. This research is a descriptive analysis. The data collected was analyzed qualitatively. The results of this study indicate that the mechanism for selling NFTs on opensea is having a balance of cryptocurrency or Ethereum money through a MetaMask wallet, having an account, owning an NFT work, determining the price, how long will the NFT last last uploading the NFT on opensea. Buying and selling NFT is a little different because it uses blockchain technology and the lens of Islamic economic law for the mechanism for selling NFT at Opensea. Looking at the pillars of sale and purchase, the actual NFT transaction process is not fulfilled, because the value or means of exchange (saman) contains gharar and dharar. . The results of the Ijtima Ulama Fatwa MUI decision stated that the use of cryptocurrency as legal currency is unlawful, because it contains gharar, dharar and contradicts Law Number 7 of 2011 and Bank Indonesia Regulation Number 17 of 2015 so it cannot be used as a transaction tool because in practice there are discrepancy with the pillars of the sale and purchase contract. However, it must be acknowledged that the world continues to develop and technology is increasingly sophisticated, it does not rule out the possibility that one day NFT will be legalized. To show that Islam is salihun likulli epoch wa likulli eat (suitable for all times and places), academic ijtihad must be carried out to answer contemporary muamlah problems in the era of globalization.